CUSTOMER LOYALTY MEDIATED BY CUSTOMER SATISFACTION WITH PRODUCT QUALITY, SERVICE QUALITY AND PRICE PREDICTORS IN THE SELLING SECTOR OF C MINING MATERIALS IN ACEH BESAR DISTRICT - Jordiansyah; Muslim; Utami, Sorayanti (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examines the impact of product quality, service quality, and price on customer satisfaction and loyalty in the Class C mining materials sector in Aceh Besar Regency. Aceh Besar Regency was selected as the research location due to its status as the largest producer of Class C mining materials in the region. The study population comprised all customers who purchased Class C mining materials in the Banda Aceh and Aceh Besar areas. The sample was selected using a purposive sampling technique, resulting in a total of 210 respondents. The collected data were analyzed using Structural Equation Modeling (SEM) with AMOS. The findings indicate that product quality, service quality, and price collectively function effectively. Moreover, these three factors exhibit a significant relationship with customer satisfaction. The analysis further reveals that product quality, service quality, and price influence customer loyalty, both directly and indirectly through customer satisfaction as a mediating variable. Consequently, customer satisfaction serves as a critical link between product quality, service quality, and price in fostering customer loyalty. These findings offer valuable insights for business managers in the Class C mining materials industry in Aceh Besar Regency, emphasizing the importance of enhancing product quality, service, and pricing strategies to improve customer satisfaction and loyalty..